The animo Timpag people in the development of tourism villages in Bali - I Wayan Kiki Sanjaya; Gede Yoga Kharisma Pradana; I Gusti Ayu Praminatih; Made Arya Astina; I Ketut Muliadiasa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The goal of this study is to identify possible areas for tourism development in Tabanan Regency, Bali namely in Timpag Village. In Tabanan, It’s a relatively new tourist destination. The success of other tourists villages in Bali seem to inspire the Timpag villagers to enhance their tourism potential. This research aims to reveal the factors that make Timpag villagers interested in building a tourist village and inventory the tourism potential. Therefore, the sample is those selected in Timpag village by purposive sampling. The research was conducted using qualitative methods. Data was gathered through observations and literature reviews. Each data set was analyzed using qualitative techniques. This research found that animo as a social interest is an important factor in the development of tourist villages. The research findings indicate that: First, the Timpag people are eager to develop the village’s tourism potential and have shown social solidarity by prioritizing the creation of tourist infrastructures. Many forms of tourism solidarity were not caused by the role of the pokdarwis. The tourism animo has become a huge internal factor for the Timpag people for their tourism village; Second, Timpag Village has potential for natural tourism, cultural tourism, ecotourism, and special interest tourism. It has developed based on capital and social commitment based on their tourism animo. Some of the tourism potential hasn’t developed optimally due to the lack of support from pokdarwis, resistance from some Timpag communities, and lack of local government assistance for tourism development in Timpag village.